Ewing sarcoma – pathomechanisms, standard treatment and new therapeutic perspectives - Zezuliński, Wojciech; Woliński, Filip; Zyśk, Julia; Korga, Mateusz; Klas, Jakub; Baj, Jacek; Dzierżyński, Eliasz (Quality in Sport, 2025)
Introduction: Ewing sarcoma is the second most common bone tumor among children, and due to its high malignancy 5-year survival rate for patients with primary lesions is around 70%. This number drops to merely 30% if metastases are present. Despite combined modality treatment, including radiotherapy, surgery, pre- and post-surgery chemotherapy, the mortality of patients is still too high. This shows a great need to look for new therapeutic options. Methodology: Comprehensive literature review was conducted across databases, including PubMed and Google Scholar for studies published between 2000 and 2023. This review presents factors that play a key role in pathogenesis and are potential points of targeted therapy. The paper discusses, among other things, treatment attempts based on the role of the EWS-FLI1 protein, epigenetics, tyrosine kinase inhibitors, immunotherapies and the use of nanomedicine and viruses, as well as the difficulties associated with their application. Findings: The studies cited vary depending on the phase of the clinical trial they are on, of which teprotumumab, robatumumab, and a combination of cixutumumab/temsyrolimus, ivodesinib, Nivolumab (a PD-1 inhibitor), and Ipilimumab (a CTLA-4 inhibitor) are quite advanced as well as those conducted only on animals and in vitro like YK-4-279 molecule, mithramycin 2'-oxime, NK cells, siRNAs with cationic detonation nanodiamonds (DNDs) and Il-12 by means of lentiviruses. Conclusions: They are new and promising approaches in cases where standard treatments fail, yet they still require further study. Knowledge of the mechanisms of Ewing's sarcoma formation and its metastases, currently accepted treatment standards, critical points in the pathomechanism and current attempts at treating Ewing's sarcoma is essential for choosing the best treatment and effectively reducing its mortality rate.